JKN Patient Satisfaction Analysis Based on Reliability Dimension at Islamic Dental Hospital and the mouth (RSIGM) of Sultan Agung Semarang - Niam, Mohammad Husnun; Putri, Natasya Ayu; Suhartono, Budi; Putranto, R. Rama (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Patient satisfaction is one of the indicators of service quality that is greatly influenced by the level of patient satisfaction to get more patients. Patients will give good references or assessments to others on the quality of health services received. Patients will always choose quality health services, according to their needs, can meet their expectations and desires. Objective: This study aims to determine the reliability dimension of the satisfaction level of JKN patients at the Islamic Dental and Oral Hospital (RSIGM) SA Semarang. Methode: This study applied of descriptive observational research (case study) using an accidental sampling technique of 97 respondents. The research instrument used a questionnaire consisting of 8 items of reliability dimension questions on JKN patient satisfaction. The research instrument used was the distribution of questionnaires offline. The test of research results uses validity, reliability, and descriptive tests. Results: The study used a validity test with an interval value of 0.361 from all reliability dimension questions with a total value of >0.6. The quality of service in the reliability dimension on JKN patient satisfaction at RSIGM SA Semarang has a correlation coefficient value of 0.896. Conclusion: There is an overview of the application of the reliability dimension to the level of satisfaction of JKN patients. The better the application of the reliability element that is applied, the better the level of patient satisfaction will be given.